The Relationship Between Business Licensing and Public Service Effectiveness: A Study on MSMEs in the Service Sector - Agustine Susi Mulyati; Pandri Zulfikar; Donny Ferdiansyah; Muhammad Ali Mustofa; Toyib Zainal; Majuri Majuri (Citakonsultindo, 2026)
This study examines the relationship between business licensing and the effectiveness of public services, focusing on Micro, Small, and Medium Enterprises (MSMEs) in the service sector. The research is grounded in the transformation of licensing systems from conventional bureaucratic procedures to digital, risk-based approaches such as the Online Single Submission Risk-Based Approach (OSS-RBA). Using a qualitative descriptive method based on literature review, this study analyzes how licensing reforms influence efficiency, accessibility, transparency, and user satisfaction in public service delivery. The findings indicate that digital licensing systems significantly improve service effectiveness by simplifying procedures, reducing processing time, and enhancing transparency. However, challenges such as limited digital literacy, technological constraints, and institutional coordination issues still hinder optimal implementation. The study concludes that while licensing reform has a positive impact on public service effectiveness, its success depends on supporting factors including human resource capacity, infrastructure readiness, and policy consistency. This research contributes to the discourse on governance reform and MSME empowerment in developing economies. Keywords: Business licensing; Public service effectiveness; MSMEs; Digital governance